Downregulation of CHCHD2 may Contribute to Parkinson’s Disease by Reducing Expression of NFE2L2 and RQCD1 - Li, Kelu; Ning, Pingping; Liu, Bin; Yang, Hongju; Zhu, Yongyun; Yin, WeiFang; Zhou, Chuanbin; Ren, Hui; Yang, Xinglong (Current Neurovascular Research, 2022)
Background: Parkinson’s disease (PD) is associated with coiled-coil-helix-coiled-coilhelix domain containing 2 (CHCHD2) downregulation, which has been linked to reduced cyclocytase activity and increased levels of oxygen free radicals, leading to mitochondrial fragmentation and apoptosis. Little is known about how CHCHD2 normally functions in the cell and, therefore, how its downregulation may contribute to PD. Objective: This study aimed to identify such target genes using chromatin immunoprecipitation sequencing from SH-SY5Y human neuroblastoma cells treated with neurotoxin 1-methyl-4- phenylpyridinium (MPP+) as a PD model. Methods: In this study, we established a MPP+ -related SH-SY5Y cell model and evaluated the effects of CHCHD2 overexpression on cell proliferation and apoptosis. At the same time, we used high-throughput chromatin immunoprecipitation sequencing to identify its downstream target gene in SH-SY5Y cells. In addition, we verified the possible downstream target genes and discussed their mechanisms. Results: The expression level of α-synuclein increased in SH-SY5Y cells treated with MPP+, while the protein expression level of CHCHD2 decreased significantly, especially after 24 h of treatment. Chip-IP results showed that CHCHD2 might regulate potential target genes such as HDX, ACP1, RAVER2, C1orf229, RN7SL130, GNPTG, erythroid 2 Like 2 (NFE2L2), required for cell differentiation 1 homologue (RQCD1), solute carrier family 5 member 7 (SLA5A7), and NAcetyltransferase 8 Like (NAT8L). NFE2L2 and RQCD1 were validated as targets using PCR and western blotting of immunoprecipitates, and these two genes together with SLA5A7 and NAT8L were upregulated in SH-SY5Y cells overexpressing CHCHD2. Downregulation of CHCHD2 may contribute to PD by leading to inadequate expression of NFE2L2 and RQCD1 as well as, potentially, SLA5A7 and NAT8L. Conclusion: Our results suggest that CHCHD2 plays a protective role by maintaining mitochondrial homeostasis and promoting proliferation in neurons. In this study, the changes of CHCHD2 and downstream target genes such as NFE2L2/RQCD1 may have potential application prospects in the future. These findings provide leads to explore PD pathogenesis and potential treatments.
Keywords: RQCD1